Antiplatelet Therapy Monitoring in Neonates and Children - Huang, Joanna Yilin; Soeharto, Diajeng Ayesha; Damara, Ivan; Ignjatovic, Vera; Linden, Matthew D.; Monagle, Paul (Seminars in Thrombosis and Hemostasis, 2019)
Antiplatelet agents are used for the prevention and treatment of thromboembolic disease in an increasingly complex population of pediatric patients. Despite their importance for clinical outcome, there is no consensus on the most effective monitoring strategies. This review describes the current state of knowledge focusing on antiplatelet therapy monitoring in children. The authors searched five databases (PubMed-NCBI, MEDLINE-OVID, SCOPUS-Elsevier, ScienceDirect, and Cochrane) from January 2000 to October 2017 using keywords selected a priori. Identified articles were sorted according to the antiplatelet agents administered, methods of antiplatelet monitoring, and outcome measures. Twenty studies were included, with 14 cohort studies, 3 randomized controlled trials, and 3 cross-sectional studies. Eleven different antiplatelet monitoring tools were used, with the most common being Light Transmission Aggregometry, Urinary Thromboxane, Thromboelastography with Platelet Mapping, and VerifyNow. In the majority of studies, antiplatelet therapy monitoring was used to describe adequacy or responsiveness to treatment based on laboratory cut-off values, which were not uniform and sourced from adult studies or extrapolated from test manuals. Several studies evaluated monitoring related to clinical outcome or adjusted therapy to reach predefined therapeutic targets. There was no single laboratory method found to be distinctly better for monitoring antiplatelet treatment. Associations between laboratory assays and clinical outcomes or assays and gold standard measurements were highly inconsistent. The current literature lacks consensus on clinical benefits and measurable effects of monitoring antiplatelet therapy in pediatric patients. This review highlights important areas for research required to determine the value of antiplatelet therapy monitoring in children.
Keywords: antiplatelet therapy; monitoring; child; therapy; prevention